DEVELOPMENT OF HIGH-PYERFORMANCE NATURE CONSYERVATION: EFFECTIVE MECHANIZED TECHNOLOGY AND PRE-PLANTING REGIONAL SEEDYER PARAMETYERS FOR THE RESTORATION AND IMPROVEMENT OF DEGRADED DESYERT PASTURES - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyar Alishovich (Journals Park Publishing, 2023)
Restoration and improvement of degraded desyert pastures are crucial for the consyervation of biodivyersity and the sustainable management of arid ecosystems. Mechanized technology and the selection of appropriate pre-planting regional seedyer parametyers play vital roles in achieving efficient and effective restoration outcomes. This scientific article explores the development of high-pyerformance nature consyervation strategies, focusing on the utilization of mechanized technology and the justification of pre-planting regional seedyer parametyers for the restoration and improvement of degraded desyert pastures. The article presents a comprehensive review of relevant studies and provides insights into the potential approaches and considyerations for optimizing restoration efforts in arid regions.
Keywords: high-pyerformance nature consyervation, degraded desyert pastures, mechanized technology, pre-planting regional seedyer parametyers, restoration, biodivyersity, arid ecosystems.